2021
DOI: 10.3389/fpls.2021.633227
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Subgroup 6 R2R3-MYB Genes and Their Contribution to Floral Color in the Perianth-Bearing Piperales

Abstract: Flavonoids, carotenoids, betalains, and chlorophylls are the plant pigments responsible for floral color. Anthocyanins, a class of flavonoids, are largely responsible for the red, purple, pink, and blue colors. R2R3-MYB genes belonging to subgroup 6 (SG6) are the upstream regulatory factors of the anthocyanin biosynthetic pathway. The canonical members of these genes in Arabidopsis include AtMYB75, AtMYB90, AtMYB113, and AtMYB114. The Aristolochiaceae is an angiosperm lineage with diverse floral groundplans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…It was found that only VcMYB1 contained the sg6-motif among the genes up-regulated in blueberries ( Figure 3B ). Studies have shown that the sg6 motif can promote the synthesis of plant anthocyanins ( Stracke et al, 2001 ; Muñoz et al, 2021 ). For further verification, Phylogenetic analysis of all the excavated VcMYB protein sequences and homologous sequences of other 138 species of plants showed that only the VcMYB1 gene has extremely high homology with the Arabidopsis SG-6 R2R3 MYB protein ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that only VcMYB1 contained the sg6-motif among the genes up-regulated in blueberries ( Figure 3B ). Studies have shown that the sg6 motif can promote the synthesis of plant anthocyanins ( Stracke et al, 2001 ; Muñoz et al, 2021 ). For further verification, Phylogenetic analysis of all the excavated VcMYB protein sequences and homologous sequences of other 138 species of plants showed that only the VcMYB1 gene has extremely high homology with the Arabidopsis SG-6 R2R3 MYB protein ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Two species‐specific subgroups (S6 and S24) only contain AtMYBs. Subgroup 6 (AtMYB75, AtMYB90, AtMYB113, and AtMYB114) and Subgroup 24 (AtMYB53, AtMYB92, and AtMYB93) have been shown to be involved in the regulation of anthocyanin and suberin biosynthesis, respectively (Legay et al, 2015 ; Munoz‐Gomez et al, 2021 ; To et al, 2020 ). These species‐specific genes suggest that these proteins might have specialized roles that have been either lost or gained after divergence from their last common ancestor.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, subgroup 5 is wellknown to play crucial roles in the positive regulation of proanthocyanidin biosynthesis so that the TwMYB in this group might also play similar roles(Wang et al, 2019). There were three species-specific R2R3-MYB subgroups (S27, S28, and S29) in Tripterygium wilfordii.Two species-specific subgroups (S6 and S24) only contain AtMYBs.Subgroup 6 (AtMYB75, AtMYB90, AtMYB113, and AtMYB114) and Subgroup 24 (AtMYB53, AtMYB92, and AtMYB93) have been shown to be involved in the regulation of anthocyanin and suberin biosynthesis, respectively(Legay et al, 2015;Munoz-Gomez et al, 2021;To et al, 2020). These species-specific genes suggest that these proteins might have specialized roles that have been either lost or gained after divergence from their last common ancestor.…”
mentioning
confidence: 99%
“…While CaMYB31 is reported to involved in regulation of biosynthesis of capsaicinoids in Capsicum annum [12], DkMyb4 regulated proanthocyanidin biosynthesis in persimmon [13]. A number of MYBs linked to anthocyanin biosynthesis were identi ed in many species, such Arabidopsis (AtMYB75, AtMYB90, AtMYB113 and AtMYB114) [14][15][16], citrus (CsRuby1 and CsMYB3) [17] and tomato (SlMYB12) [18] whereas others involved in cellular morphogenesis, secondary cell wall biosynthesis, meristem formation and cell cycle regulation [19][20][21][22]. A rice R2R3-MYB gene (OsCSA) directly triggers expression of sugar partitioning and metabolic genes during pollen and seed development [23].…”
Section: Introductionmentioning
confidence: 99%